Platform network ties and enterprise innovation performance: The role of network bricolage and platform empowerment - Ying Han; Lei Xie (Journal of Innovation & Knowledge, 2023)
Small and medium-sized enterprises (SMEs) that participate in network platforms can effectively overcome resource bottlenecks and reduce the impact of the coronavirus pandemic of 2019. However, the reasons for this phenomenon remain unclear. To further investigate this issue, we selected 310 Chinese SMEs to examine the relationship between platform network ties, network bricolage, platform empowerment, and enterprise innovation, including both radical and incremental innovation. The empirical results demonstrate that platform network ties can enhance enterprises’ innovation performance. Furthermore, the empirical verification of this study's assumptions provides evidence that network bricolage mediates the relationship between network ties and enterprises’ innovation performance, while platform empowerment plays a moderating role. The study results could potentially contribute to the more effective management of platform networking ties, empowerment, and bricolage, thus benefiting the management of SMEs.